Effective Work Breakdown Structures - Haugan, Gregory (Berrett-Koehler Publishers, 2001)
At last - the first comprehensive and practical guide to the work breakdown structure (WBS) in 45 years! This book offers vital new perspectives on how to apply the WBS to today's different types of projects that produce products, services or results. You'll learn how to use WBS throughout the project lifecycle to plan, control and communicate. Your new insights into the WBS principles, plus checklists and proven action steps, will improve the planning of new projects and help you launch projects more efficiently and effectively.